2020
DOI: 10.3390/polym12030646
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Properties, Secondary Structure, and Osteogenic Activity of Photopolymerized Fibroin

Abstract: Previously, we have described the preparation of a novel fibroin methacrylamide (FbMA), a polymer network with improved functionality, capable of photocrosslinking into Fb hydrogels with elevated stiffness. However, it was unclear how this new functionality affects the structure of the material and its beta-sheet-associated crystallinity. Here, we show that the proposed method of Fb methacrylation does not disturb the protein’s ability to self-aggregate into the stable beta-sheet-based crystalline domains. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…After 21 days (longest time point assessed) in osteogenic culture, the TCP (elastic modulus ∼3 GPa) and the PLTMC 80/20 G (12 kPa) induced significantly higher calcium deposition and ALP activity than the other groups. This is in accordance with previous literature in the field showing that high in stiffness substrates [67][68][69][70] and/or surfaces with topographical features [24,26,[71][72][73] enhance in vitro osteogenesis. Interestingly, the PLTMC 80/20 G induced an improved (higher, but not significant) increase in calcium deposition and a significant increase in ALP activity over the planar PLTMC 80/20 calcium deposition, whilst the PGCL 10/90 G induced significantly lower calcium deposition and improved (higher, but not significant) ALP activity over the planar PGCL 10/90.…”
Section: Stem Cell Differentiation Analysissupporting
confidence: 93%
“…After 21 days (longest time point assessed) in osteogenic culture, the TCP (elastic modulus ∼3 GPa) and the PLTMC 80/20 G (12 kPa) induced significantly higher calcium deposition and ALP activity than the other groups. This is in accordance with previous literature in the field showing that high in stiffness substrates [67][68][69][70] and/or surfaces with topographical features [24,26,[71][72][73] enhance in vitro osteogenesis. Interestingly, the PLTMC 80/20 G induced an improved (higher, but not significant) increase in calcium deposition and a significant increase in ALP activity over the planar PLTMC 80/20 calcium deposition, whilst the PGCL 10/90 G induced significantly lower calcium deposition and improved (higher, but not significant) ALP activity over the planar PGCL 10/90.…”
Section: Stem Cell Differentiation Analysissupporting
confidence: 93%
“…A series of in-vitro tests proved that this design can be used as a detector for multimicrofluidic immunoassays [36]. Bessonov et al also developed a novel fibroin methacrylamide which can be photocrosslinked into hydrogels and improve their mechanical properties [37]. In addition, their studies showed that their modified polymer increases osteoinductive activity, including increasing cell numbers, rearranging actin cytoskeleton, and improving distribution in focal contacts, indicating that this modified substrate can be used in tissue engineering applications.…”
mentioning
confidence: 99%